Prevalence and trends of drugged driving in Canada. (February 2017) - Robertson, Robyn D.; Mainegra Hing, Marisela; Pashley, Charlotte R.; Brown, Steve W.; Vanlaar, Ward G.M.
Highlights: Self-reported drugged driving behaviours from 2002 to 2015 in Canada were analyzed. Drug tests of fatally injured drivers from 2000 to 2012 in Canada were analyzed. There was an increase in self-report driving after using marijuana (2013–2015). There was an increase in percent of fatally injured drivers positive for drugs. Overall, male and young drivers had higher prevalence of drugged driving. Abstract: Objectives: This study evaluates prevalence and trends in drugged driving in Canada based on multiple indicators collected from the Road Safety Monitor (RSM) and Canada's National Fatality Database maintained by the Traffic Injury Research Foundation (TIRF). The objective of this paper is to identify the state of drug-positive driving in Canada, as well as to make comparisons with data from previous years to determine whether changes have occurred. Methods: Available data from the RSM on self-reported drugged driving behaviours were collected and analyzed using multivariate techniques in various years spanning from 2002 to 2015. Data from TIRF's National Fatality Database from 2000 to 2012 were also analyzed to evaluate trends and prevalence of drugs in fatally injured drivers across Canada. Additionally, differences among drugged drivers with respect to gender and age were studied. Results: Analyses of the RSM data and of the National Fatality Database showed that, as a whole, the prevalence of drugged driving has remained relatively stable over the past decade, with some changes noticed in specific years for some drug types. Specifically from the RSM, there was a 62.5% increase from the 1.6% of drivers reporting driving within two hours of using marijuana in 2013 to 2.6% in 2015. The analyses of the fatality data revealed a 16.9% increase in the percentage of fatally injured drivers testing positive for drugs between 2000 and 2012 (from 33.56% to 39.24%). Cocaine-positive fatally injured drivers increased from 3.6% in 2000 to 6.2% in 2012. Similarly, marijuana-positive fatally injured drivers increased from 12.8% in 2000 to 19.7% in 2012. Results showed varying characteristics with respect to gender and age among self-reported and fatally injured drugged drivers. Conclusions: Drugged driving behaviours remain prevalent among Canadian drivers and drugs continue to be found in over one-third of tested fatally injured drivers. Although self-reported behaviours have neither decreased nor increased overall in the past decade according to RSM data, with the exception of driving within two hours of using marijuana, data from fatally injured drivers reveal that small, but significant increases in some behaviours have occurred.